2023
DOI: 10.1109/twc.2022.3222781
|View full text |Cite
|
Sign up to set email alerts
|

Link Scheduling Using Graph Neural Networks

Abstract: To reduce the latency of Backpressure (BP) routing in wireless multi-hop networks, we propose to enhance the existing shortest path-biased BP (SP-BP) and sojourn time-based backlog metrics, since they introduce no additional time step-wise signaling overhead to the basic BP. Rather than relying on hopdistance, we introduce a new edge-weighted shortest path bias built on the scheduling duty cycle of wireless links, which can be predicted by a graph convolutional neural network based on the topology and traffic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Using a resource provisioning scheme, they considered the problem of optimizing and managing the resource. The authors formulated the resource allocation based on the Graph Convolutional Networks (GCNs) [18]. They have proved that the proposed method gains significant improvement concerning communication complexity in wireless networks [19].…”
Section: Related Workmentioning
confidence: 99%
“…Using a resource provisioning scheme, they considered the problem of optimizing and managing the resource. The authors formulated the resource allocation based on the Graph Convolutional Networks (GCNs) [18]. They have proved that the proposed method gains significant improvement concerning communication complexity in wireless networks [19].…”
Section: Related Workmentioning
confidence: 99%
“…These researcher considered the issue of controlling and optimizing the resource while using a strategy for resource supply. The resource allocation was created by the authors using GCNs [ 40 ]. They showed that the suggested technique greatly lowers the wireless networks’ communication complexity [ 41 ].…”
Section: Related Workmentioning
confidence: 99%
“…Recent research has employed Graph Neural Networks (GNNs) as an innovative solution to overcome challenges in wireless networks. Zhao et al [45] addressed the issue of link scheduling in these networks. They conceptualized the problem as a maximum weight independent set issue, and put efficient approximations for the problem, based on a GNN and guided tree search.…”
Section: B Joint Routing and Tdma Link Schedulingmentioning
confidence: 99%